(untitled) (Perner’s Contacts, 2019)
The scientific article is dedicated to tires and the pressure they exert on the road surface. In the paper, we have defined the main structural elements of a tire. We analysed the dimensions of the contact areas and compared the measured values with the calculated ones. The article also deals with legislative conditions in road construction. In the next section we compare the design axle with the contact surfaces of the most frequently used tires. The results are summarized in tables and with a percentage difference. Based on this analysis, we came to the conclusion which tires have an impact on the road. At the end of the article we present possible solutions tothe problem with their advantages and disadvantages.